Desempenho produtivo e qualitativo de cultivares de alho semi-nobre vernalizado na Mesorregião Oeste Potiguar - Lucena, Rafaella Rayane Macedo de (Universidade Federal Rural do Semi-Árido, 2015)
Garlic is one of the vegetables of great economic and social relevance in Brazil. Among the consumer states, Rio Grande do Norte, especially, despite having regions with favorable conditions for growing garlic, currently, depends on imports of this product to meet its domestic demand. The introduction of more productive and quality cultivars, better market acceptance, and adjustments of vernalization technology, a key issue for adaptation of new cultivars, are mechanisms that can contribute to garlic revitalization in areas previously producing this vegetable. In order to evaluate the development, production and quality semi-noble garlic cultivars under different periods of pre-planting vernalization of seed bulbs in two city in the Mesoregion West Potiguar, we developed two experiments, simultaneously in Baraúna and Governador Dix-sept Rosado, between the months of April and November 2012. The experimental design was a randomized complete block design with four replications. The treatments were arranged in a split plot, being the plots represented by semi-noble cultivars Gigante do Núcleo and BRS Hozan and subplots consisted by periods of vernalization before planting the seed bulbs at 4 ± 1 ° C: 0, 10, 20 and 30 days. We evaluated: plants emergency, plant height, leaf number, cultural cycle, final stand, mass fresh total, percentage of bulbs differentiation of bulbils, bulbils number, classification of bulbils, bulb average weight, yield total, classification bulbs, diameter of bulb, pH, titratable acidity, soluble solids, total soluble sugars, reducing sugars, pungency, total solids and industrial index. The vernalization did not provide increases significant in productivity, however, the use of 10 day of the vernalization pre-planting seed bulbs allowed in improving the quality of garlic semi-noble produced in Baraúna and Governador Dix-sept Rosado. The cultivars Gigante do Núcleo (4.56 t ha-1) and BRS Hozan (4.42 t ha-1) had higher yields in Baraúna. In this city, garlic produced showed greater diameter, pungency and total solids, with higher industrial index therefore better quality for industrialization (processing or dehydration)
Productive and qualitative performance of semi-noble garlic cultivars vernalizated in Mesoregion West Potiguar
Keywords: Garlic; refrigeration; Vegetable - growing garlic; Vernalization; Quality and production - garlic; Alho; Frigorificação; Hortaliça - cultivo de alho; Vernalização; Qualidade e produção - alho; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA